Gender and contemporary horror in comics, games and transmedia - Shail, Robert; Holland, Samantha; Gerrard, Steven (Emerald studies in popular culture and gender, 2019)
Contemporary popular media has been marked by its startling ability to morph into a wide variety of formats, fed by the ongoing revolution in digital technology. Despite these significant changes, the horror genre has retained its attraction for audiences, and the representation of gender has been crucial to that appeal.Gender and Contemporary Horror in Comic, Games and Transmedia examines the impact of media convergence on the horror genre, focusing on comic books and graphic novels, video games, audio broadcasts, and transmedia adaptations, as well as considering the increasingly proactive role of audiences in making media themselves. A wide range of scholars consider the effect of this new hybridity on established debates regarding the role of gender in the horror genre, offering vital new interpretations of identity and representation.This book is an illuminating, exciting read for academics and students interested in the effect of changing media, and an evolving cultural landscape, on the established debates surrounding gender in the horror genre. The responses of the authors reflect both the possible limitations and the groundbreaking possibilities of this new era in horror.